Novel Assays to Distinguish Between Properdin-Dependent and Properdin-Independent C3 Nephritic Factors Provide Insight Into Properdin-Inhibiting Therapy - Michels, Marloes A. H. M.; van de Kar, Nicole C. A. J.; van den Bos, Ramon M.; van der Velden, Thea J. A. M.; van Kraaij, Sanne A. W.; Sarlea, Sebastian A.; Gracchi, Valentina; Oosterveld, Michiel J. S.; Volokhina, Elena B.; van den Heuvel, Lambertus P. W. J. (Frontiers in Immunology, 2019)
C3 glomerulopathy (C3G) is an umbrella classification for severe renal diseases characterized by predominant staining for complement component C3 in the glomeruli. The disease is caused by a dysregulation of the alternative pathway (AP) of the complement system. In more than half of C3G patients C3 nephritic factors (C3NeFs) are found. These autoantibodies bind to the AP C3 convertase, prolonging its activity. C3NeFs can be dependent or independent of the complement regulator properdin for their convertase-stabilizing function. However, studies to determine the properdin-dependency of C3NeFs are rare and not part of routine patient workup. Until recently, only supportive treatments for C3G were available. Complement-directed therapies are now being investigated. We hypothesized that patients with properdin-dependent C3NeFs may benefit from properdin-inhibiting therapy to normalize convertase activity. Therefore, in this study we validated two methods to distinguish between properdin-dependent and properdin-independent C3NeFs. These methods are hemolytic assays for measuring convertase activity and stability in absence of properdin. The first assay assesses convertase stabilization by patient immunoglobulins in properdin-depleted serum. The second assay measures convertase stabilization directly in patient serum supplemented with the properdin-blocking agent Salp20. Blood samples from 13 C3NeF-positive C3G patients were tested. Three patients were found to have properdin-dependent C3NeFs, whereas the C3NeF activity of the other ten patients was independent of properdin. The convertase-stabilizing activity in the samples of the patients with properdin-dependent C3NeFs disappeared in absence of properdin. These data indicate that inhibition of properdin in patients with properdin-dependent C3NeFs can normalize convertase activity and could represent a novel therapy for normalizing AP hyperactivity. Our assays provide a tool for identifying C3G patients who may benefit from properdin-inhibiting therapy and can be incorporated into standard C3G laboratory investigations.